Peningkatan Ketrampilan Pelaku UMKM Kuliner untuk Paguyuban, Dusun Kronggahan, Gamping, Sleman, Yogyakarta - Musaroh, Musaroh; Buana Muslim, Bintang Lazuardi Benteng; Margasari, Naning; Laili, Nindya Nuriswati (Rahmatan Lil 'Alamin Journal of Community Services, 2025)
The purpose of this community service activity is to improve the business management skills of culinary MSME business actors in the Kronggahan area, Gamping. The training provided includes business management training and MSME skills improvement training which is carried out by providing training on variations in making bright moon culinary with various flavours. This service activity was arranged by the service team in an activity programme in the form of training delivered face-to-face. The training participants are estimated to consist of 30 people who work as culinary MSME players. The materials presented were culinary business management training and product diversification. products and various flavours of martabak products according to the demand of the target audience. The service activities were carried out in the form of training, socialisation and discussion for culinary business actors in the Kronggahan area of Yogyakarta Special Region. The first activity was carried out offline through face-to-face meetings with a total of 30 participants with socialisation material for entrepreneurial activities. The second activity was also carried out offline, namely through activities to provide skills to culinary business actors in diversifying selling products, namely martabak and terang bulan with various flavours, which were given by resource persons we brought in from culinary experts. A total of 30 participants attended the offline activity.